Pengaruh Gender, Penghargaan Finansial, dan Pertimbangan Pasar Kerja terhadap Minat Mahasiswa Akuntansi untuk Berkarir Menjadi Akuntan Publik - Hadisti, Merly; Sari, Vita Fitria (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to determine and analyze the influence of gender, financial rewards, and job market considerations on accounting students' interest in pursuing a career as a public accountant (an empirical study of undergraduate accounting students at state and private universities in Padang City). This type of research is a causal quantitative study. The population of the study was all accounting students in Padang City. The sample selection used the cluster sampling method. The research sample was 354 accounting students. The data analysis technique in this study used multiple linear regression analysis. Based on the hypothesis testing, it can be concluded that the gender variable has a positive and significant effect on accounting students' interest. The financial rewards variable has a positive and significant effect on accounting students' interest. The job market consideration variable has a positive and significant effect on accounting students' interest.